Students’ Perception of Using Moodle as a Learning Management System in Tertiary Education - Muhammad Arifin; Imas Eryani; Ghina Farahtika (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of the study was to determine students' perspectives of utilising Moodle as a learning management system throughout the Ninth Semester. The researcher employed the descriptive qualitative research method due to its suitability for gathering data on students' perceptions. The researcher conducted interviews to collect the data. The data was acquired from the ninth semester, which was studied using Moodle. The sample consisted of 10 students, selected based on specific criteria. The research findings revealed that the students' interviews demonstrated a predominantly favourable assessment of Moodle as a learning management system, with a heightened inclination towards active participation in the learning process. Some students claimed that Moodle is hindered by network issues and server errors, which prevent them from using it. Furthermore, it was discovered that Moodle offered benefits such as effortless access to learning materials and the ability for students to manage their time effectively. Drawbacks include insufficient explanation and poor interaction.